1996
DOI: 10.1079/bjn19960094
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of lipogenesis in the lower VLDL secretion induced by oligofructose in rats

Abstract: Dietary supplementation with oligofructose (Om; 100 g/kg), a nodigestible oligomer of /h-fructose, decreases serum triacylglycerols in serum and VLDL of rats. In order to investigate the role of hepatic metabolism in the hypolipidaemic effect of Om, male Wistar rats were fed on a standard diet with or without 1OOg Raftilosee P d k g as OFS source for 30d. OFS feeding (1) significantly decreased triacylglycerol and phqholipid concentrations in both blood and liver, (2) increased the glycerol-3-phosphate liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
2
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(98 citation statements)
references
References 49 publications
5
86
2
5
Order By: Relevance
“…The same authors postulated that modi®cations of insulin plasma levels evaluated in their study could, at least in part, explain the metabolic effect of FOS. Effects on insulin could also be reinforced by increased levels of portal acetate and propionate derived from colonic fermentation and, in effect, it has been reported that portal concentration of acetate and propionate increase more than two-fold in FOS-treated rats (Kok et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same authors postulated that modi®cations of insulin plasma levels evaluated in their study could, at least in part, explain the metabolic effect of FOS. Effects on insulin could also be reinforced by increased levels of portal acetate and propionate derived from colonic fermentation and, in effect, it has been reported that portal concentration of acetate and propionate increase more than two-fold in FOS-treated rats (Kok et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of inulin and Table 9 Correlation coef®cients between independent variables (faecal bacteria counts) and dependent variables (serum lipids). Data points are from eleven subjects considered over four experimental times (total n 44), signi®cance levels are reported as P Effect of inulin on lipids and micro¯ora F Brighenti et al FOS on serum lipids has been consistently reported in different animal studies using either rats (Levrat et al, 1991, Delzenne et al, 1993, Kok et al, 1996, Fiordaliso et al, 1995 or hamsters (Trautwein et al, 1998). However, results in humans are less conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context they are known as prebiotics (Gibson & Roberfroid, 1995). FOS in addition reduces serum triglycerides in rats and diabetic humans (Fiordaliso et al, 1995;Kok et al, 1996;Yamashita et al, 1984). They are used by the food industry as low-calorie substitutes for sugar and fat.…”
Section: Mixture Syntheticmentioning
confidence: 99%